The foreign experience of providing affordable housing - Fisunenko, P.; Dzuba, S.; Fisunenko, N. (Ways to Improve Construction Efficiency, 2020)
The necessity of providing the population with proper living conditions in general, and affordable housing, in particular, is one of the most pressing problems of modern Ukraine. In terms of both quantitatively and qualitatively factors, the solution of this problem our country is significantly inferior to other developed countries, including the USA, Germany, China. Assuming that the usage of the foreign experience with considering the national characteristics, the solution to this problem would be faster and more constructive, the purpose of the article is to analyze the systems (models) of housing affordability and exploring the possibility of using them in the modern state housing policy of Ukraine. The urgency of solving the problem of providing the population with houses is increased by the lack of modern effective methods of attracting investment in construction that would improve living conditions and have a multiplier effect for the entire national economy. The article examines the foreign experience of providing affordable housing, examines the financing systems for affordable housing, which reflect the basis of the state policy of housing affordability: "German", "American" and "Chinese". The maintenance of the population with houses is analyzed, domestic and foreign approaches to determining the nature of affordable housing, as well as directions of state support in the housing sphere, are considered. The peculiarities of the financing system for housing affordability by American (mortgage), German (contract-savings) and Chinese models are given. As a rule, the developed credit facility mechanism that enables low-income households to buy housing is an important feature of foreign countries' housing policies in general, and affordable housing in particular. It is noted that to maintain the affordability of housing construction in Ukraine, it is necessary to improve the legal framework and to develop measures to increase investment in construction, which, according to world experience, can be based on mortgage or contractual-savings (joint investment) forms.